RANCANG BANGUN SISTEM INFORMASI MANAJEMEN MUTU PERUSAHAAN MENGGUNAKAN FRAMEWORK LARAVEL DAN MATERIALIZE (Studi Kasus: Bagian Pengendalian Dokumen PT. Pura Barutama Divisi Boxindo, Kudus) - Stefan Fernando; Andeka Rocky Tanaamah; Agustinus Fritz Wijaya (CCIT Journal, 2017)
Quality management is one of important aspects in the company for keep the quality of service and gaining trust from its customers, however there are some problems in monitoring the quality and performance audit result, audit schedule distribution, and ISO 9001:2008 document distribution. Therefore it needs to be managed with an integrated database system.The Purpose of this research is to design and build information system of quality management to help monitoring the quality and performance audit result, audit schedule distribution, and helps the management of ISO 9001:2008 document.System development model in this research used prototyping method. The test results using Black Box Testing Methods and interview with users indicated that the developed Information System of Quaity Management (ISQM) has been functioning in accordance with the expected functional and operational requirements.